Илюзията за едно лесно начало: Политическите и социалните дълбини на една африканска новела - Chalakova, Iliyana (Lyuboslovie, 2024)
The short prose “I wish I was a wave” won for its author Manuel Rui the fame of a master of satire in the recent history of the Angolan literature. In his worldwide recognised book, which has been translated into several languages, Rui skillfully uses irony to build a text that is, at its core, an incredible political parody and a sharp social critique of the public life in the capital Luanda in the early years after the country's independence from Portugal. The present paper focuses on the political and social layers that overlap and intertwine, building the plot architecture of this seemingly children's story. The research explores the nature of the political metaphors embedded in the fable, bearing in mind the national problems that the Angolan society faced during the last three decades of the 20th century. The study aims to outline the specific dimensions of the socio-political framework and interpret their significance for the difficult beginning of Angola's independent historical path, marked by the failed attempt at identity definition and the bloody Civil War fueled by ideological motives. The study uses instruments from the field of the literary theory, post-colonial and cultural studies, and the sociology of literature. The main result of the study is the first contact of the Bulgarian readers with a text of Manuel Rui. Other results refer to the controversial situation of the contemporary Angolan society and the capacity of the literary text to discuss it, as well as the satire‘s ability to go against the illusions and its faculty for building connections between distant cultural and literary realities, like the Angolan and the Bulgarian one.